The accidental bride - Feather, Jane. (New York : Bantam Books, 1999)
"In my "Brides" trilogy, three unconventional young women vow they will never marry -- only to be overtaken by destiny. The Accidental Bride could only be the story of Phoebe, the "awkward" one ... "-- P. [4] of cover.
Keywords: Love stories; Historical fiction; England -- Social life and customs -- 15th century -- Fiction